2013
DOI: 10.1002/anie.201309389
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Photodissociative Ruthenium Complex by Triplet–Triplet Annihilation Upconversion in Liposomes

Abstract: Liposomes capable of generating photons of blue light in situ by triplet-triplet annihilation upconversion of either green or red light, were prepared. The red-to-blue upconverting liposomes were capable of triggering the photodissociation of ruthenium polypyridyl complexes from PEGylated liposomes using a clinical grade photodynamic therapy laser source (630 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
166
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 33 publications
5
166
0
3
Order By: Relevance
“…Although our group previously demonstrated that blue-light sensitive Ru polypyridyl complex could be effectively activated by a red-to-blue TTA-UC in liposomes (Figure 1b), this demonstration was performed under argon, which is not relevant for clinical applications [26,27]. In the first part of this article, we report that it is possible to solve this issue by using the antioxidant strategy mentioned above.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although our group previously demonstrated that blue-light sensitive Ru polypyridyl complex could be effectively activated by a red-to-blue TTA-UC in liposomes (Figure 1b), this demonstration was performed under argon, which is not relevant for clinical applications [26,27]. In the first part of this article, we report that it is possible to solve this issue by using the antioxidant strategy mentioned above.…”
Section: Introductionmentioning
confidence: 85%
“…TTA-UC has been demonstrated in various organic, inorganic, and/or supramolecular materials [15,[18][19][20][21][22], as well as in nano-or micro-sized particles [23][24][25]. For biological applications, i.e., for drug delivery and activation [26,27] or bio-imaging [13,[28][29][30][31][32][33], one of the main problems of TTA-UC is its sensitivity to molecular oxygen, which readily quenches the triplet state chromophores involved in the TTA-UC mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…32 Because the emission intensity from quenched samples was low (<1%), we adopted a procedure described by Askes et al 33 In this procedure, absorption/scatter at the excitation wavelength and emission from the sample/reference were acquired under the same instrument settings (λ ex = 400 nm; 5 nm excitation slit; 0.3 nm emission slit; scan 390−410 nm for scatter/absorption; scan 500−850 nm for emission). However, the absorption/ scatter scans were measured with a neutral density filter, with known absorption (OD = 3; 0.1% transmittance), placed between the integrating sphere and the monochromator/ detector.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…17,18 Typically, complexes are designed incorporating sterically encumbered ligands that weaken metal-ligand bonds and thus stabilise 3 MC states with respect to the 3 MLCT states when compared to complexes where such encumbrance is absent. This thereby increases the thermal accessibility of 3 MC states from photoexcited 3 MLCT states [19][20][21][22][23][24][25] (the terms stabilisation and destabilisation here refer to changes in the energies of these 3 MLCT and 3 MC states with respect to each other and the ground state when comparing complexes, for example, with the archetypical [Ru(bpy) 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%